Old bottle new wine? The evolution of China's aid in Africa 1956–2014. Issue 7 (3rd July 2019) - Morgan, Pippa; Zheng, Yu
Abstract: China's aid is frequently portrayed as a challenger to established Overseas Development Assistance (ODA) norms, but it is unclear when the distinct 'Chinese-model' of aid emerged and how it has evolved over time. Using new historical data on Chinese aid in Africa and the case of Ethiopia, we have three main findings. First, China developed a distinct model of mixing ODA-like aid and commercial forms of economic engagement only after the mid-1990s, reflecting institutional reforms for allocating and managing foreign official finance. Second, social sectors have played a much greater role in China's aid programme than is commonly perceived. Finally, Chinese aid to productive sectors has changed substantially whereas in social sectors it is relatively consistent.